Mainmise, 1970: Situating Québec within Planetary Geographies - Tayler, Felicity (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2018)
In the politically-charged atmosphere of 1970s Québec, the French-language countercultural magazine Mainmise reprinted an image of a meeting in Algeria between Black Panther leader, Eldridge Cleaver and American countercultural icon, Timothy Leary. Taking this image as a case study, this article discusses the reproduction, representation, and reception of “Blackness” in Mainmise, as it is enabled through print technologies. Multi-lingual translation, transposition of texts and images between cultural contexts, and circulation to multiple readerships characterize the magazine’s rejection of Left-neo-nationalist positions. Instead, the cumulative pages of Mainmise propose a reinvented Québécois identity that is unhinged from territory or ethnic ancestry. Québec is imagined in terms of a planetary geography.